PERAN CSR PRODUK KOSMETIK TERHADAP LOYALITAS PELANGGAN KOTA BATAM - Ardila -; Renny Christiarini (JWM (JURNAL WAWASAN MANAJEMEN), 2023)
This study aims to analyze the factors that influence customer loyalty in the use of cosmetic products. Data were collected through the distribution of online questionnaires through Google Forms with 430 respondents. The population of this research is people in Batam City who have used cosmetic products from brands that have CSR such as The Body Shop, L'Oreal, Estee Lauder, Kiehl's, Garnier, Innisfree, Wardah, Emina, Somethinc, Avoskin, Sensatia Botanicals, and BLP Beauty. This study utilizes a sampling technique with non-probability sampling and purposive sampling. The collected data will be processed using the Partial Least Squares research method. The study results are that customer satisfaction, customer trust, perceived product quality, perceived service quality, perceived cost, corporate social responsibility, and customer engagement all influence customer behavior in terms of loyalty.